A review of islamic credit card concepts from shari’ah perspective in Malaysia - Md Faruk, Abdullah; Abubakar, Balarabe (2020)
The Islamic credit card is introduced by Islamic financial institutions to substitute the conventional credit card. Islamic credit card has played a significant part in the progress of Islamic banking in Malaysia. A group of contemporary scholars has an unfavourable opinion on credit card operations. They argue that it is a modern way of reviving riba and a hilah (trick) to legitimise interest. The majority disapproved of the concepts of Inah and Tawarruq of the Islamic scholars in the Hambali, Maliki and Hanafi schools of jurisprudence and some contemporary scholars considered them as sales contracts intended as a legal stratagem to legalise debt with riba (interest). However, this problem drove some Malaysian Islamic banks to come up with the concept of Ujrah, which is accepted by the more significant number of scholars as to the best substitute for Inah and Tawarruq. This study aims at reviewing the scholars’ views on the concept of Inah, Tawarruq and Ujrah applied in the Islamic credit card. The study will examine the views of classical and contemporary scholars on the concept of Inah and Tawarruq. It will then further discuss the concept of Ujrah. A qualitative method was used by adopting library research and the study mostly relied on primary and secondary sources of Shariah. The study relies on the Quran, Hadith and jurisprudence to achieve the objective. The findings highlighted that the credit cards based on the concept of ujrah (fee) are acceptable to contemporary scholars. However, modern scholars disallowed the Islamic credit card based on the concept of Inah and Tawarruq because the majority of the classical scholars have controversial of the concept of Inah and Tawarruq are legal stratagem to legitimise riba.